Divination, Greece and Rome - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2013)
Divination (Greek mantike, Latin divinatio) encompasses all forms of interrogating the gods. Contrary to general belief, its purpose is not merely to “know the future.” Confronted with any immediate choice entailing unknown repercussions, the consultant depends on divination in order to act effectively and be released from excessive anxiety, when too many hidden things remain inaccessible to his reason.